EVALUASI ATAS PENERAPAN KEBIJAKAN AKUNTANSI PENGHAPUSAN BARANG MILIK NEGARA PADA KANTOR WILAYAH DJP JAKARTA BARAT - Adhani, Ida; Thomas Dwi , Handoko (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
The aim of this research is to examine in more depth to study, evaluate and provide input on matters related to accounting policies for State Property. The data analysis technique used is by the author conducting interviews or asking questions related to state property to employees of the West Jakarta DJP Regional Office and qualitative techniques that prioritize informative descriptions related to application systems and depictions in tabular form. In implementing the accounting policy for writing off State Property at the West Jakarta Regional Office of the Directorate General of Taxes which is regulated by the Minister of Finance through Circular Letter number SE-36/MK.01/2014 and the procedures are outlined in Minister of Finance Regulation number PMK-86/PMK. 06/2016 assisted using the Agency Level Financial Application System (SAKTI). From the evaluation of the accounting policy for the write-off of State Property at the West Jakarta Regional Office of the Directorate General of Taxes in 2020, it can be concluded that the implementation of the write-off of State Property has been carried out properly in accordance with applicable government procedures and regulations.